Scientific American. – 1866. – Vol. 14, № 19 - б/а (New York. Munn & Company, 1866)
A weekly journal of practical information, art, science, mechanics, chemistry and manufacture.
Scientific American. Vol. 14, № 15-26. – New York, 1866. – P. 223-442.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Economic history; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES::Physics; Research Subject Categories::NATURAL SCIENCES::Chemistry; May 5, 1866; Recent American Patents; Patents; Improved Cider Mill; Clayton’s Cider Mill; Rand’s Device for Centering Saws; Schooley’s Fodder Cutter; Jeanne’s Pipe; Bugbee’s Crutch; Helmkamp’s Self-Rocking Cradle; Ladenberger’s Shock Arrester